Socioeconomic Gradient and Anthropometric Risk: Central Obesity among Adolescents in Aceh, Indonesia - Siti Maisyaroh Fitri Siregar; Wan Ain Nadirah Che Wan Mansor; Arfah Husna; Lili Eky Nursia N (Contagion: Scientific Periodical Journal of Public Health and Coastal Health, 2026)
Central obesity is a critical risk factor for future cardiometabolic disorders in adolescents, particularly in low- and middle-income settings such as Indonesia. This cross-sectional study examined the prevalence and determinants of central obesity among adolescents in Aceh Barat and Nagan Raya, Indonesia. A total of 167 senior high school students were recruited using purposive sampling, which allowed representation from multiple schools but limits generalizability beyond the study population. Data on waist circumference, family income, physical activity, screen time, and body mass index (BMI) were collected using standardized procedures. Central obesity was defined based on age- and gender-specific waist circumference cut-offs according to International Diabetes Federation criteria. Associations were examined using chi-square tests and binary logistic regression. The prevalence of central obesity was 15.0%. In bivariate analysis, adolescents from middle–high income families (OR = 3.23; 95% CI: 1.35–7.75) and those classified as overweight based on BMI (OR = 40.30; 95% CI: 12.69–127.98) had significantly higher odds of central obesity. However, in multivariate analysis, only BMI remained independently associated with central obesity (AOR = 0.02; 95% CI: 0.005–0.083), while socioeconomic status, physical activity, and screen time were no longer statistically significant Keywords: Adolescents, Body Mass Index, Obesity Central, Socioeconomic Status, Screen Time